Effect of Verticillium lecanii entomopathogen of the Whitefly Trialeurodes vaporariorum on the parasitic activity of Amitus fuscipennis in a bean culture - PACHÓN, MARÍA DEL PILAR; COTES-P., ALBA MARINA (Revista Colombiana de Entomología, 1997)
In order to evaluate the effect of the entomopathogen Verticillium lecanii against the whitefly parasitoid A. fuscipennis bioassays were performed under greenhouse and field conditions. Greenhouse bioassays were carried out at 70% relative humidity and 25°C of temperature. The parasitoid A. fuscipennis was introduced 0,24,48 y 72 hours after the application of V lecanii in bean leaves containing whitely nymphs of the second instar. Under these conditions, the fungus V lecanii decreased the parasitic activity of A. fuscipennis with the course of time. When the parasitoid was introduced immediately after the fungi applications, A. fuscipennis parasitism percentage was 19%, and after 24 hours parasitism level was 10%. The activity of A. fuscipennis to parasitize whiteflies decreased at 0.5% after 48 and 72 hours of entomopathogen application. In spite of the decrease of A. fuscipennis parasitic activity, V lecanii never infected directly the beneficia) insect A. fuscipennis. For the field assays, the entomopathogen was applied every 10 days for 80 days after sowing. These applications were performed as two preformulátions of V lecanii developed by Corpoica, and as a commercial product based on V lecanii recommended for whiteflies control (Vertisol). This experiment also included an absolute control and a treatment of Integrated Pest Management (MIP) that consisted of the application of a granular insecticide during the sowing, the use of yellow and adhesive traps, and the application of chemical insecticide when the damage level increased. The statistical analysis for the results showed significant differences between all evaluations and the one made after 40 days of sowing. Corpoica preformulátions did not affect significantly the parasitism activity of A. fuscipennis. The percentage parasitism obtained when these products were used was 15 %, whereas commercial treatment (Vertisol) reduced A. fuscipennis parasitism level at 7% in contrast with MIP treatment that showed a A. fuscipennis leve] of parasitism of 17% while absolute control showed parasitism of 23%.